2006
DOI: 10.1039/b515464b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of atomic hydrogen on ZnO(101̄0): STM study

Abstract: The adsorption of atomic hydrogen on a single crystal ZnO(1010) surface has been studied by scanning tunneling microscopy (STM) under ultrahigh vacuum conditions at room temperature and at elevated temperatures. High resolution STM images indicate that a well-ordered (1x1) H adlayer is formed on the ZnO(1010) surface. The STM data strongly indicate that the hydrogen adsorbs on top of the oxygen atoms forming hydroxyl species. Scanning tunneling spectroscopy (STS) studies reveal a H atom induced metallization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 30 publications
8
41
0
Order By: Relevance
“…Therefore, the present reactivity data for the nonpolar (11À20) surface agrees with the instability characterizing this surface reported by Diebold and coworkers. [25,26] In contrast, for the nonpolar (10À10) surface, previous studies [12,23] have shown that above room temperature only one hydrogen atom on the O site per unit cell is present, indicating that atomic hydrogen adsorbs on the O-sites only, forming hydroxyl groups. On increasing the temperature, desorption of H 2 O as well as of Zn hydrides result in a loss of oxygen as well as of ZnO dimers, as reported by Woll and coworkers, [12,23] therefore explaining the observed roughening and damage of (10À10) ZnO.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the present reactivity data for the nonpolar (11À20) surface agrees with the instability characterizing this surface reported by Diebold and coworkers. [25,26] In contrast, for the nonpolar (10À10) surface, previous studies [12,23] have shown that above room temperature only one hydrogen atom on the O site per unit cell is present, indicating that atomic hydrogen adsorbs on the O-sites only, forming hydroxyl groups. On increasing the temperature, desorption of H 2 O as well as of Zn hydrides result in a loss of oxygen as well as of ZnO dimers, as reported by Woll and coworkers, [12,23] therefore explaining the observed roughening and damage of (10À10) ZnO.…”
mentioning
confidence: 67%
“…Therefore, it is of great importance from both fundamental and technological viewpoints to study the interaction of ZnO with atomic hydrogen, taking into account any interplay of polarity and of crystalline properties of the ZnO itself. Previously, Woll and coworkers [12,19,23] investigated the adsorption of hydrogen on the nonpolar mixed (10À10) m-plane of ZnO (which is the lowest-energy surface of ZnO [24] and does not exhibit a fixed polarization surface charge like Zn-and O-polar ZnO [7] ), with the aim of investigating how hydrogen atoms were arranged on the (10À10) surface. However, no previous investigations have been reported on the interaction of hydrogen with the mixed (11À20) surface, and contradictory results are also reported about its stability.…”
mentioning
confidence: 99%
“…Unfortunately, the number of such experiments performed with the STM is surprisingly small. Most of them deal with polar ZnO(0001) surfaces, 361,363 or explore the hydroxylation of thin oxide films with polar character, for instance of Cr 2 O 3 /Cr(110) 402 or more recently of FeO/Pt(111). 303 For the latter system, also experiments on other atomic and molecular adsorbates have been performed with low-temperature STM, which shall be presented in the following.…”
Section: Adsorption On Polar Oxide Filmsmentioning
confidence: 99%
“…35 Also the interaction of hydrogen with oxide defects has been addressed at the atomic level. 363 Water exposure to the ZnO(10-10) leads to the formation of compact ad-islands with a (2×1) super-structure. 311 366 bulk samples, investigating the interaction of water and carboxylic acid with the oxide surface, respectively.…”
Section: Fig 46mentioning
confidence: 99%
See 1 more Smart Citation